An R2R3-MYB Transcription Factor RmMYB108 Responds to Chilling Stress of Rosa multiflora and Conferred Cold Tolerance of Arabidopsis - Dong, Jie; Cao, Lei; Zhang, Xiaoying; Zhang, Wuhua; Yang, Tao; Zhang, Jinzhu; Che, Daidi (Frontiers in Plant Science, 2021)
Sudden cooling in early spring or late autumn negatively impacts plant growth and development. Although a number of studies have characterized the role of plant R2R3-MYB (R2R3-myeloblastosis) transcription factors (TFs) in biotic and abiotic stress response, plant growth, and primary and specific metabolisms, much less is known about their role in Rosa multiflora under chilling stress. In the present study, RmMYB108, which encodes a nuclear-localized R2R3-MYB TF with self-activation activity, was identified based on the previously published RNA-seq data of R. multiflora plants exposed to short-term low temperature stress and on the results of gene function prediction referring Arabidopsis. The RmMYB108 gene was induced by chilling, salt, and drought stresses, and was expressed to higher levels in roots than in leaves. Heterologous expression of RmMYB108 in Arabidopsis thaliana significantly enhanced the tolerance of transgenic plants to freezing, water deficit, and high salinity, enabling higher survival and growth rates, earlier flowering and silique formation, and better seed quantity and quality compared with the wild type (WT) plants. When exposed to continuous low temperature stress at 4°C, transgenic Arabidopsis lines overexpressing RmMYB108 showed higher superoxide dismutase and peroxidase activities, lower relative conductivity and malondialdehyde content than the WT. Moreover, the initial fluorescence (Fo) and maximum photosynthetic efficiency of photosystem II (Fv/Fm) changed more dramatically in the WT than in transgenic plants. Furthermore, the expression levels of cold-related genes involved in the Inducer of CBF expression 1 (ICE1)- C-repeat binding factors (CBFs)- Cold regulated genes (CORs) cascade were higher in OE lines than in the WT. These results suggest that RmMYB108 was positively involved in the tolerance responses when R. multiflora under cold, freeze, salt, or drought challenges, and improved the cold tolerance of transgenic Arabidopsis by reducing plant damage and promoting plant growth.